Techno-economic assessment of cooperation of hybrid renewable energy sources with hydrogen storage - Łukasik, Jakub; Jewartowski, Marcin; Wajs, Jan (Instal, 2023)
The paper presents a technical and economic analysis of the power supply for a model industrial facility with the use of the most promising renewable energy sources (RES), supported by a hydrogen energy storage. This scenario was compared with the variants of supplying the facility directly from the grid and from RES without energy storage. A strategy was proposed for powering the plant aimed at maximising self-consumption of self-generated electricity. In this paper the importance of hybrid renewable energy systems (HRES) with hydrogen energy storage in the Polish Power System is pointed out. For the analysed industrial object, the modelling and optimisation of the systems were performed in the HOMER software, in terms of the lowest net present cost. Attention was also paid to the need to compress hydrogen and the associated electricity consumption.